The contribution of rsha mutations and efflux pumps in tigecycline resistance in abscessus - Aw, Kar Men (2022)
Tigecycline is an important antibiotic in treating patients with Mycobacteroides abscessus infections. Tigecycline resistance was previously associated with dysregulated stress response induced by the abnormal interaction between the SigH and RshA factors. Two laboratory-derived tigecycline-resistant mutants (CL5A and CL6A) which possessed mutations in the rshA gene and upregulated efflux pumps were studied, to have a better understanding on the role of rshA mutations and efflux pumps in tigecycline resistance in M. abscessus. Gene complementation studies confirmed that the rshA mutations in the mutants caused tigecycline resistance. The assumption that rshA mutations disrupt the interaction between RshA and SigH factors was tested using the Bacterial Adenylate Cyclase Two-Hybrid (BACTH) assay. The results showed that the RshA-SigH interaction in the rshA mutant was indeed slower than in the positive controls. RT-qPCR analyses on the mutants showed an upregulation of the sigH gene which indicated the release of SigH following the disrupted RshA-SigH interaction. Three efflux genes (MAB_1395, MAB_1396 and MAB_1299c) were also found to be upregulated. This indicated that efflux pumps may contribute to tigecycline resistance in M. absccessus. However, overexpression of the three efflux genes did not result in any significant increase in tigecycline resistance. This suggested that the upregulation of efflux genes seen was a consequence of a rshA mutation, but was not, on its own, the cause of tigecycline resistance in this mutant . This study demonstrated that disrupt the inte rshA mutations in M. abscessus could raction between RshA and SigH, two proteins that are transcriptional regulators of physiological stress response in mycobacteria. The disrupted interaction is believed to lead to the overexpression of causes M. abscessus to be resistant against sigH which tigecycline. The mechanism which SigH causes tigecycline resistance has yet to be elucidated. The role of efflux pumps in tigecycline resistance in M. abscessus requires further exploration.